Dinamika Umat di Masa Pandemi COVID-19: Lingkup Pribadi - Palmoko, Yohanes Aji; Kurniawan, Antonius Jery; Pasati, Yohanes Dwi Penta (Felicitas, 2021)
This research wants to see how far the faith of the people is still being nurtured by the presence of the covid pandemic which limits all activities including church activities, especially regarding the spiritual life of the people, both in devotional prayer and the Eucharist. The author took samples from 5 parishes in the city of Surabaya, namely the Sacred Heart of Jesus (31 respondents), Santo Yusuf - Karangpilang parish (108 respondents), Santo Aloysius Gonzaga parish (83 respondents), Santa Maria Immaculate - Ngagel parish (114 respondents), and the parish of St. James-Citraland (35 respondents). By referring to the “Social Teaching of the Church” of Pope Francis, the author will reflect on the results of the research.